EVALUASI KEBISINGAN LALU LINTAS DI KOTA PEKANBARU - Indra Hasan; Erwin Erwin; Zulkarnaini Zulkarnaini; Isranuri Isranuri (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2019)
Noise is unwanted sound that might be disturbing public life especially in urban area. Pekanbaru is one of big city in Indonesia. The rapid increase of economic growth will impact to the number of vehicles that cross over the roads. The purpose of this research is to study the phenomenon of traffic noise sourced by vehicle. The measurements were performed to the eight of main roads in Pekanbaru city. And the result showed the traffic noise which exceeded the threshold of public health. Preventive action should be conducted to mitigate the noise pollution.